Functional contacts for activation of urease from Helicobacter pylori: an integrated approach using evolutionary couplings, in-cell enzymatic assays, and computational docking - Carosella, Noemi; Brock, Kelly P.; Zambelli, Barbara; Musiani, Francesco; Sander, Chris; Ciurli, Stefano (Frontiers in Chemical Biology, 2023)
Urease is an enzyme exploited by many virulent bacteria and fungi to infect the host and exert their virulence. The Gram-negative bacterium Helicobacter pylori relies on the activity of urease to infect the highly acidic human stomach. The activity of urease depends on the presence of a catalytic site containing two Ni(II) ions. In vivo, urease is initially synthesized as an inactive apo-enzyme and requires a post-translational activation process that involves the incorporation of the metal ions into its buried active site. In H. pylori, as well as in other bacteria, this activation process is mediated by four accessory proteins, named UreD, UreF, UreG, and UreE. Targeting the interactions between urease chaperones could potentially inhibit the activation of urease through blocking the Ni(II) ions incorporation, providing a route for the development of antimicrobial strategies against ureolytic pathogens. In this paper, an evolutionary couplings (EC) approach was adopted to determine the interaction surface between urease and UreD, the first protein that binds the enzyme, preparing it for the subsequent activation steps. The EC prediction retrieved ten pairs of residues lying at the interface between UreD and the urease subunit UreB, likely involved in contacts essential to build the protein complex. The functional importance of these contacts was evaluated using site-directed mutagenesis and an assay to detect urease activity in recombinant bacteria expressing the mutated operon. The obtained data were used to drive a protein-protein docking computational approach that led to the obtainment of a model for the urease-UreD complex that agrees well with the recently reported experimental cryo-EM structure. This work represents a proof of concept for the calculation of reliable models of protein interaction surfaces in the absence of experimental structures of critical assemblies.